2005
DOI: 10.1021/bm049347a
|View full text |Cite
|
Sign up to set email alerts
|

Caprolactonic Poloxamer Analog:  PEG-PCL-PEG

Abstract: The aqueous solution of poly(ethylene glycol)-poly(caprolactone)-poly(ethylene glycol) (PEG-PCL-PEG) triblock copolymers (> 15. wt. %) undergoing "clear sol-gel-turbid sol" transition as the temperature increases from 20 to 60 degrees C has been developed. Light scattering and 13C NMR study suggested that the transition mechanisms are the micellar aggregation for the clear sol to gel transition (lower transition), whereas the increase in PCL molecular motion for gel to turbid sol transition (upper transition).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
242
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(251 citation statements)
references
References 20 publications
8
242
1
Order By: Relevance
“…Recently, PEG-PCL-PEG and PCL-PEG-PCL (Scheme 5) triblock copolymers have been introduced, and aqueous solutions thereof showed a clear sol-to-gel-to-turbid sol transition with an increase in temperature. [31,32] DLS and 13 C NMR studies indicated that the clear sol-to-gel transition arose from micellar aggregation, whereas the gel-to-turbid sol transition was driven by the breakage of the core-shell structure. Because of differences in structural topology, PCL-PEG-PCL had a higher G 0 (10 000 Pa) ( Figure 4) than did PEG-PCL-PEG (100 Pa) ( Figure 5).…”
Section: Poly(ethylene Glycol) (Peg)/polyestermentioning
confidence: 99%
“…Recently, PEG-PCL-PEG and PCL-PEG-PCL (Scheme 5) triblock copolymers have been introduced, and aqueous solutions thereof showed a clear sol-to-gel-to-turbid sol transition with an increase in temperature. [31,32] DLS and 13 C NMR studies indicated that the clear sol-to-gel transition arose from micellar aggregation, whereas the gel-to-turbid sol transition was driven by the breakage of the core-shell structure. Because of differences in structural topology, PCL-PEG-PCL had a higher G 0 (10 000 Pa) ( Figure 4) than did PEG-PCL-PEG (100 Pa) ( Figure 5).…”
Section: Poly(ethylene Glycol) (Peg)/polyestermentioning
confidence: 99%
“…Terephthaloyl chloride (0.694 g, 3.3 mmol) and triethylamine (1.41 mL, 10.12 mmol) were added to the reaction mixtures and stirred at 60 °C for 24 h. The product was isolated by precipitation into diethyl ether, then the polymer was redissolved in 30 mL of methylene chloride, filtered, and precipitated by slowly adding diethyl ether. The residual solvent was removed under vacuum [95,[99][100][101]. Figure 4.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…First of all, number average molecular weight and molecular weight distribution of the synthesized PEG-poly(-caprolactone) copolymers were determined using gel permeation chromatography (GPC) [96,[100][101][102].…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…These micelles provide enhanced stability for lengthy drug circulation in blood owing to their low critical micelle concentration (CMC), followed by drug accumulation in solid tumors through an enhanced permeability and retention effect (EPR) [2,[4][5][6]. Among the various types of micelles, amphiphilic copolymers comprised of poly(ethylene glycol) (PEG) as the hydrophilic segments and polyesters including poly(D,L-lactic acid) (PDLLA), poly(glycolic acid) (PGA), and poly(ε-caprolactone) (PCL) as the hydrophobic segments have been extensively investigated as drug carriers due to their excellent biocompatibility and biodegradability [7][8][9][10][11][12][13]. However, the drug release inside cancer cells is often insufficient due to the highly hydrophobic and slow degrading nature of inner core-forming polyesters, which results in slow and incomplete drug release [14,15].…”
Section: Introductionmentioning
confidence: 99%